(untitled) (Research, Society and Development, 2020)
Infections caused by Cryptococus spp. are opportunistic, urban, and associated with immunosuppression. Mortality is estimated at 10% in developed countries and 43% in emerging countries. The objective was to evaluate the clinical-epidemiological aspects of cryptococcosis in the region of western São Paulo. This is a cross-sectional study, based on information from the medical records of patients in a hospital in the interior of São Paulo from 2006 to 2018. Descriptive analysis was applied through absolute (n) and relative (%) frequency; and statistics through the x2 and Fisher’s Exact tests. Relative Risk (RR) and Odds Ratio (OD) for death were also calculated. Neurocriptococcosis was the primary clinical manifestation of 64.50%. The direct search for CSF was positive in 85.71% of the samples, the immunodiagnosis in 93.80% and the culture, gold standard for fungus, in 55.55% of the cases. The x2 test and Fisher’s exact test showed no difference between sex, age group, clinical form of death. RR and OD were considered low. The association of the epidemiological aspects of cryptococcosis with its clinical signs allows the early diagnosis of the disease, reducing severe conditions. Besides, high-performance antiretroviral therapies have dramatically decreased the occurrence of deaths in patients with HIV.